Review Paper on Minimum DC Bus Voltage for AC-DC Single Stage Full Bridge Converter - Raman, Rahul Dev; Shukla, Lokesh (International Journal of Computer Sciences and Engineering, 2019)
This paper presents a single-stage circuit topology consisting of the association of a full-bridge isolated dc–dc converter and two input inductors and two input diodes connected to the mains network, in order to obtain an isolated ac/dc switch mode power supply, with sinusoidal input current. The proposed topology does not use an input bridge rectifier, common in similar applications. The current in the two input inductors can therefore, flow in both directions. Consequently, the proposed topology equally distributes the current by the four-bridge transistors that provide four input parallel boost power factor correctors (PFCs). The use of the four bridges permitting the accurate simultaneous regulation of output voltage and input current is hereby described.